An analysis of conjunctive elements in the Chinese translation of Karim Raslan’s ceritalah 3: Malaysia a dream deferred / Siew Hui Sheng - Siew, Hui Sheng (2016)
Answering the call for more linguistic-based research on local Chinese newspapers (Shao, 2012), this research is an attempt to identify cohesion shifts with the focus on conjunctions (also known as conjunctive elements in this study) in the Chinese translation of Karim Raslan’s column articles. Raslan is a renowned columnist in Malaysia. This study attempts to identify instances of explicitations/implicitations in argumentative texts. Since conjunctive elements are overt markers which can be counted, the difference in the quantity of conjunctive elements employed in the source texts and target texts can serve as a pointer to the phenomenon of explicitation/implicitation (Blum-Kulka, 1986; Klaudy, 2004; Pym 2005; Kamenicka, 2007b; Vinay and Darbelnet, 1995; Becher, 2011a). Halliday and Hasan’s (2001) cohesion model of five categories is employed as a guideline with some modifications as suggested by other linguists (Smith & Frawley, 1983, p. 355; Baker, 2001, p. 192; Hatim and Mason, 2001). Through in-depth analysis and discussions, it is found that shifts in conjunctive elements can affect a translation in five possible ways: altering the intensity of the message, shifting the focus of the message, altering the tone and manner of the texts, changing the author’s personal remarks, and construction of sentences with superfluous conjunctive elements. On top of that, wrong translations of conjunctive elements lead to undesirable results as well.